أثر تطبيق النظام المحاسبي المالي (fas) على الاستثمار الأجنبي المباشر في الجزائر - جلاخ حسين (جامعة الوادي University of Eloued, 2024)
This study aimed to determine the impact of applying the financial accounting system on attracting foreign direct investment to Algeria, by studying and analyzing foreign direct investment flows before and after adopting the financial accounting system, in addition to evaluating the Algerian investment climate by analyzing investment attractiveness indicators and comparing them with some Arab countries. By analyzing the reality of foreign direct investment in Algeria, we note that the volume of foreign direct investments is still weak despite Algeria’s adoption of the financial accounting system. There are no noticeable developments in the volume of forms after 2010. Despite the confirmation of the theoretical relationship that exists between the application of the financial accounting system and attracting investment, foreign direct investment has other political, social, legal and tax determinants that prevent Algeria from attracting foreign investors. Therefore, Algeria must work on processed.
The impact of implementing the Financial Accounting System (FAS) on Foreign Direct Investment (FDI) in Algeria
Keywords: استثمار أجنبي مباشر; نظام محاسبي مالي; مناخ الاستثمار